Analysis of Preplate Splitting and Early Cortical Development Illuminates the Biology of Neurological Disease - Olson, Eric C. (Frontiers in Pediatrics, 2014)
The development of the layered cerebral cortex starts with a process called preplate splitting. Preplate splitting involves the establishment of prospective cortical layer 6 (L6) neurons within a plexus of pioneer neurons called the preplate. The forming layer 6 splits the preplate into a superficial layer of pioneer neurons called the marginal zone and a deeper layer of pioneer neurons called the subplate. Disruptions of this early developmental event by toxin exposure or mutation are associated with neurological disease including severe intellectual disability. This review explores recent findings that reveal the dynamism of gene expression and morphological differentiation during this early developmental period. Over 1000 genes show expression increases of ≥ 2 fold during this period in differentiating mouse L6 neurons. Surprisingly, 88% of previously identified non-syndromic intellectual disability (NS-ID) genes are expressed at this time and show an average expression increase of 1.6 fold in these differentiating L6 neurons. This changing genetic program must, in part, support the dramatic cellular reorganizations that occur during preplate splitting. While different models have been proposed for the formation of a layer of L6 cortical neurons within the preplate, original histological studies and more recent work exploiting transgenic mice suggest that the process is largely driven by the coordinated polarization and coalescence of L6 neurons rather than by cellular translocation or migration. The observation that genes associated with forms of NS-ID are expressed during very early cortical development raises the possibility of studying the relevant biological events at a time point when the cortex is small, contains relatively few cell types, and few functional circuits. This review then outlines how explant models may prove particularly useful in studying the consequence of toxin and mutation on the etiology of some forms of NS-ID.